Conjoined twins: report of two cases and review of literature - Rathod, Setu; Samal, Sunil Kumar (International Journal of Research in Medical Sciences, 2017)
Two pairs of conjoined twins were encountered at the SCB medical college cuttack, Odisha, India during the past 3 years. In the first set the prenatal diagnosis was not established and the case was referred to us from other hospital with diagnosis of twin pregnancy and prolonged second stage of labour. Emergency caesarean section done and a pair of thoraco-omphalopagus twins delivered. Both babies died soon after birth. In the second case the conjoined twins were diagnosed prenatally at 20 weeks of gestationon in routine anomaly scan as thoraco-omphalopagus twin with fetuses were positioned face-to-face and fused from sternum to umbilicus. Fetuses were found to have separate hearts, a fused liver and separate upper and lower gastrointestinal tracts. Each twin had two normal appearing kidneys and a urinary bladder. The couples were counselled about the various management options and referred to higher centre. But she was admitted at 34 weeks of gestation with preterm labour and emergency caesarean section done and a pair of male thoraco-omphalopagus twins delivered. Both babies were alive and referred to higher centre for further management. The prenatal identification of conjoined twins is of cardinal importance for the planning of delivery and possible separation.